2020
DOI: 10.1016/j.cedpsych.2020.101843
|View full text |Cite
|
Sign up to set email alerts
|

Researchers’ achievement goals: Prevalence, structure, and associations with job burnout/engagement and professional learning

Abstract: Researchers' motivations are important for high-quality research and the productivity of the scientific system, but remain largely uninvestigated. Using three studies, we tested the usefulness of Achievement Goal Theory (AGT) for describing research motivations, investigated which goals researchers pursue, and examined their associations with job burnout/engagement and professional learning. Interviewing 20 researchers (Study 1), we found that most of their goals in the research context were classifiable as ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 110 publications
3
43
0
Order By: Relevance
“…Different affective, cognitive, and behavioral consequences have been documented for preferences for different goals in diverse populations, such as students, athletes, and teachers (Hulleman et al, 2010;Payne, Youngcourt, & Beaubien, 2007). Lately, AGT has also successfully been used to describe the motivations of university scholars (Daumiller & Dresel, 2020;Daumiller, Dickhäuser, & Dresel, 2019;Daumiller, Figas, & Dresel, 2015;Daumiller, Grassinger, Dickhäuser, & Dresel, 2016;Janke & Dickhäuser, 2018;Janke, Rudert, & Daumiller, 2018). These research works documented that university scholars report pursuing different achievement goals that can empirically be considered as distinct from each other and that are differentially associated with aspects of their cognition and behavior (such as attitudes towards help-seeking, experience of positive affect, learning behaviors, and questionable research practices) as well as students' assessments of teaching quality and their learning outcomes.…”
Section: University Scholars' Achievement Goals For Teaching and Resementioning
confidence: 99%
See 3 more Smart Citations
“…Different affective, cognitive, and behavioral consequences have been documented for preferences for different goals in diverse populations, such as students, athletes, and teachers (Hulleman et al, 2010;Payne, Youngcourt, & Beaubien, 2007). Lately, AGT has also successfully been used to describe the motivations of university scholars (Daumiller & Dresel, 2020;Daumiller, Dickhäuser, & Dresel, 2019;Daumiller, Figas, & Dresel, 2015;Daumiller, Grassinger, Dickhäuser, & Dresel, 2016;Janke & Dickhäuser, 2018;Janke, Rudert, & Daumiller, 2018). These research works documented that university scholars report pursuing different achievement goals that can empirically be considered as distinct from each other and that are differentially associated with aspects of their cognition and behavior (such as attitudes towards help-seeking, experience of positive affect, learning behaviors, and questionable research practices) as well as students' assessments of teaching quality and their learning outcomes.…”
Section: University Scholars' Achievement Goals For Teaching and Resementioning
confidence: 99%
“…These research works documented that university scholars report pursuing different achievement goals that can empirically be considered as distinct from each other and that are differentially associated with aspects of their cognition and behavior (such as attitudes towards help-seeking, experience of positive affect, learning behaviors, and questionable research practices) as well as students' assessments of teaching quality and their learning outcomes. In doing so, these investigations regarded achievement goals in the teaching domain (Daumiller et al, 2019;Daumiller et al, 2015;Daumiller et al, 2016), or the research domain (Daumiller & Dresel, 2020;, or the overall university work context without distinguishing between teaching and research (Janke & Dickhäuser, 2018).…”
Section: University Scholars' Achievement Goals For Teaching and Resementioning
confidence: 99%
See 2 more Smart Citations
“…To this end, studies have found motivational quality (such as achievement goals) to be an important factor for explaining these individual differences (e.g., Lemyre, Hall, & Roberts, 2008;Mäkikangas & Kinnunen, 2016). Specifically, the motivational systems spanned up by focusing on different achievement goals can be considered as resources or determinants of primary and secondary appraisals of stressors (Folkman, Lazarus, Dunkel-Schetter, DeLongis, & Gruen, 1986; see Daumiller & Dresel, 2020). As mastery approach goals are focused on competence development, athletes who strongly endorse such goals may view stressful and exhausting achievement situations as positive and controllable learning opportunities, leading to associations with decreased burnout levels, while the opposite can be expected for individuals who are worried about failure and perceive achievement situations as threatening (which is typically the case when pursuing strong avoidance goals).…”
Section: Achievement Goals and Elite Athletes' Burnout Levels And Psymentioning
confidence: 99%